Comparison of Predisposing and Effective Factors on Divorce Application between Men and Women - Nasrin Abedinia; Jafar Bolhari; Fatemeh Ramezanzadeh; Mohammad Mehdi Naghizadeh (Tehran University of Medical Sciences, 2012)
Objective: with regard to his human and social nature, sympathy is required that men and women live together in peace and rest. Since that family is manifestation and expression of life and love, divorce is a critical that consequences and undesirable effects on individuals, families and society. The present study based on gender People requesting a divorce in the family courts in Tehran has paid during the years 2006-2007. Materials and methods: The sample included 300 people referred from the courts, and cross-sectional study approach, with structured interview was conducted. Causes and reasons for divorce after the interview and identified as economic factors, psychological, cultural - social, sexual problems, physical, addiction, violence and marriage with this classification and statistical methods chi-square, Fisher and Mann - Whitney two groups were compared. Results: Results showed that although most divorce because both gender (84.4% of women and 90% of men) lack of understanding and compromise has been divorce for women, but more influenced by socioeconomic status (P< 0.001), violence (P< 0.001) sexual problems (P= 0.048) and addiction (P= 0.001), while men were more due to cultural problems - social (P= 0.023) had been demanded divorce. Conclusion: The results also suggested the counseling of premarital and to aware in the field of professional advice at the time of the divorce that it can prevent the occurrence divorce.